Faktor Faktor Penyerapan Bahasa Asing Ke Dalam Perubahan Bahasa Indonesia - Siti Rahmah Saniyah; Tasya Aulia (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This research discusses the absorption of foreign languages towards changes in the Indonesian language. History has shown that Malay (Indonesian) has absorbed many foreign languages. Absorption elements in the form of phonemes, affixes and words also enrich the Indonesian vocabulary. Positively, the presence of loan words can sharpen the power of Indonesian language expression. Efforts to limit the absorption of foreign words are not only a matter of strengthening one's personality, but also of protecting the Indonesian language system. Reality has shown that not all loan words are subject to our language system, but on the contrary, Indonesian is "forced" to make modifications to accommodate them.